JURIDICAL ANALYSIS OF BUSINESS ACTORS’ LIABILITY IN CONSUMER PROTECTION IN INDONESIA - imansyah; Muhammad Julianto (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2026)
This study examines the juridical analysis of business actors’ liability in consumer protection in Indonesia, focusing on legal regulation, forms of liability, and dispute resolution mechanisms available to consumers. The objective of this research is to analyze the legal framework governing business actors’ responsibilities and to assess its role in ensuring legal protection for consumers. This study employs normative legal research using a statutory and conceptual approach, supported by library-based data derived from legislation, legal doctrines, and relevant scholarly works. The analysis is conducted through a descriptive-analytical method to examine the relationship between legal norms and the implementation of business liability in consumer protection. The findings show that Law Number 8 of 1999 on Consumer Protection provides a comprehensive legal basis regarding the obligations of business actors, compensation for consumer losses, and mechanisms for dispute settlement through non-litigation and litigation channels. Business liability is manifested through compensation, product replacement, and other legal remedies aimed at restoring consumer rights. The study also finds that challenges remain in the implementation of liability principles, particularly regarding compliance, legal awareness, and law enforcement effectiveness. Strengthening the implementation of business actors’ liability is essential to promote justice, legal certainty, and balanced legal relations between businesses and consumers.